LncRNA DSCAM‐AS1 acts as a sponge of miR‐137 to enhance Tamoxifen resistance in breast cancer. Issue 3 (10th September 2018) - Ma, Yun; Bu, Deyong; Long, Jiang; Chai, Wenying; Dong, Jian
Abstract: Objective: To investigate the influence of long noncoding RNA (lncRNA) DSCAM‐AS1 on the propagation and apoptosis of Tamoxifen‐resistant (TR) breast cancer cells via regulation of mircoRNA (miR)‐137 and epidermal growth factor receptor pathway substrate 8 (EPS8). Methods: Data of GSE5840 downloaded from the Gene Expression Omnibus database were utilized to screen out aberrantly expressed lncRNA and messenger RNA in breast cancer tissue samples. The expressions of DSCAM‐AS1, miR‐137, and EPS8 were determined by quantitative real time polymerase chain reaction (qRT‐PCR). Cell lines were screened by half maximal inhibitory concentration (IC 50 ). 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2‐H‐tetrazolium bromide (MTT) assay and the flow cytometry assay were used to detect cell proliferation, apoptosis, and cell cycle. The relationship among DSCAM‐AS1, miR‐137, and EPS8 was studied by miRcode, TargetScan, and Pearson correlation coefficient. A xenograft mouse model experiment was performed to demonstrate the effect of DSCAM‐AS1 and EPS8 on tumor growth in vivo. Results: LncRNA DSCAM‐AS1 and EPS8 were significantly upregulated, whereas miR‐137 was downregulated in TR tissues. DSCAM‐AS1 could promote the Tamoxifen resistance of breast cancer, and it was negatively correlated with miR‐137, whereas positively correlated with the expression of EPS8 in TR breast cancer tissues. Furthermore, miR‐137 could inhibit tumor development and arrest cell cycle at the G0/G1 phase by targeting the 3′‐UTR of EPS8. DSCAM‐AS1 targeted miR‐137 and EPS8 to promote propagation of TR breast cancer cells and inhibit cell apoptosis. Conclusion: LncRNA DSCAM‐AS1 acts as a competing endogenous RNA of miR‐137 and regulates EPS8 to promote cell reproduction and suppresses cell apoptosis in TR breast cancer. Abstract : 1. DSCAM‐AS1 could modulate the expression of epidermal growth factor receptor pathway substrate 8 (EPS8) through mircoRNA (miR)‐137 in breast cancer cells, promote Tamoxifen resistance, propagation, and metastasis of cells in breast cancer, and inhibit cell apoptosis. 2. The DSCAM‐AS1/miR‐137/EPS8 axis may provide new therapeutic targets for Tamoxifen‐resistant breast cancer.